Three Doses of Platelet-Rich Plasma Therapy Are More Effective Than One Dose of Platelet-Rich Plasma in the Treatment of Knee Osteoarthritis: A Systematic Review and Meta-analysis - Tao, Xinyu; Aw, Angeline Ai Ling; Leeu, Jun Jie; Bin Abd Razak, Hamid Rahmatullah (Arthroscopy, 2023)
To compare the efficacy of a single dose of platelet-rich plasma (PRP) with multiple doses of PRP therapy in the treatment of knee osteoarthritis (KOA). The PubMed, Embase, CINAHL (Cumulative Index to Nursing and Allied Health Literature), Scopus, and Cochrane Library databases were searched from database inception to May 2022; in addition, the gray literature and bibliographic references were searched. Only randomized controlled trials comparing the effect of a single dose versus multiple doses of PRP for KOA were included. Literature retrieval and data extraction were conducted by 3 independent reviewers. The inclusion and exclusion criteria were based on type of study, research subjects, intervention, outcome, language, and availability of data. Pooled analyses of visual analog scale (VAS) scores, Western Ontario and McMaster Universities Arthritis Index scores, and adverse events were conducted. Seven studies (all randomized controlled trials) of high methodologic quality involving 575 patients were included. The ages of the patients included in this study ranged from 20 to 80 years, and the sex ratio was balanced. Triple-dose PRP therapy resulted in significantly better VAS scores compared with single-dose PRP therapy at 12 months (P < .0001), with no significant change in VAS scores between double-dose PRP and single-dose PRP at 12 months. Regarding adverse events, double-dose (P = .28) and triple-dose (P = .24) therapy showed no significant differences in safety from single-dose therapy. Although there is a paucity of large high-quality Level I studies, current best evidence suggests that 3 doses of PRP for KOA are more effective than 1 dose of PRP at providing pain relief up to 1 year after administration. Level II, systematic review of Level II studies.